THE ROLE OF GAME METHODS IN TEACHING A FOREIGN LANGUAGE (Journal of Universal Science Research, 2023)
This article discusses ways to learn a foreign language more conveniently through various games. Through these games, it becomes easier for schoolchildren to learn a foreign language.